Perinatal Outcomes of Twin Gestations with and without Gestational Diabetes Mellitus - Sarkar, Arjun; Caughey, Aaron B.; Cheng, Yvonne W.; Yee, Lynn M. (American Journal of Perinatology, 2022)
Objective Existing data suggest that obstetric outcomes for individuals with twin gestations, who have gestational diabetes mellitus (GDM), may be comparable to those who do not have GDM, yet studies are limited by small sample sizes. The aim of this study was to examine differences in maternal and neonatal outcomes of individuals with twin gestations based on presence of GDM.Methods This was a population-based retrospective cohort study of individuals giving birth to twins in the United States between 2012 and 2014. Inclusion criteria were live births (≥24 weeks) and available information on GDM status; individuals with pregestational diabetes were excluded. Participants were categorized as either having had or not had GDM. Multivariable logistic regression was utilized to assess the independent association of GDM with adverse maternal outcomes, whereas generalized estimating equation models were used to estimate associations with neonatal outcomes to account for clustering.Results Of 173,196 individuals meeting inclusion criteria, 13,194 (7.6%) had GDM. Individuals with GDM were more likely to be older, identify as Hispanic or Asian race and ethnicity, married, college educated, privately insured, and obese than those without GDM. After adjusting for potential confounding variables, those with GDM were more likely to have hypertensive disorders (18.0 vs. 10.2%) and undergo cesarean delivery (51.2 vs. 47.3%). Neonates born to individuals with GDM were more likely to require mechanical ventilation for greater than 6 hours (6.5 vs. 5.6%) and experience neonatal intensive care unit (NICU) admission (41.1 vs. 36.2%), but were less likely to be low birth weight or have small for gestational age status (16.2 vs. 19.5%). Findings were confirmed in a sensitivity analysis of neonates born at 32 weeks of gestation or greater.Conclusion Odds of poor obstetric and neonatal outcomes are increased for individuals with twin gestations complicated by GDM.Key Points
Keywords: gestational diabetes; twin pregnancy; pregnancy outcomes; cohort studies